Potential implications of a NSFR on German banks' credit supply and profitability - Matthias Schmitt; Christian Schmaltz (Deutsche Bundesbank, 2016)
We study how a Net Stable Funding Ratio as defined by the Basel Committee in 2014 (NSFR (2014)) would affect the profitability of German banks and their capacity to lend. With a NSFR-model that is partially calibrated against reported NSFRs, we find that 9% of German banks do not comply with the NSFR (2014). This is a significant reduction compared to the 39% that we find for its prior definition, the NSFR (2010), for the same sample. Structurally, banks that do not comply with the NSFR (2014) hold less liquid assets, rely less on retail funding, but more on short-term market funding and are more highly leveraged. A microeconomic model applied to each of the 163 non-compliant banks suggests that they would engage in 70 different strategies to become compliant. All strategies are growth strategies and none of them cuts lending. On average, banks would see their Return on Assets dropping once by moderate 10 bps. Our conclusion is that an introduction of the NSFR (2014) as minimum standard is unlikely to exhibit adverse consequences for credit supply and bank profitability.
Keywords: G21; G28; 330; NSFR; Credit supply; Profitability